Does Sense of the Humor Make Sense in the Classroom? - Freddy Antonio González-Ynfante (Universidad Nacional, Costa Rica, 2011)
This paper studies the importance of humor as a teaching strategy in the classroom, considering the usual lack of motivation and boredom. To analyze whether the "happy teaching and happy learning" may increase effectiveness in the teaching-learning process, the author will discuss how, despite the many benefits it may bring, humor is not used in the classroom due to prejudices and fears. The idea is not for teachers to play the role of a comedian or a clown, but to intervene and get closer to the group with a teaching, didactic purpose through humor. Plato (1992) thought about this; he used to say that sometimes a joke may help, where seriousness put up resistance.